Pediatric thoracic spinal Ewing sarcoma/primitive neuroectodermal tumor: a case report and literature review - Ma, Long; Li, Xiaodong; Meng, Fei; Wong, Stanley Sau Ching; Wang, Fengfeng (Frontiers in Pediatrics, 2025)
The Ewing sarcoma/primitive neuroectodermal tumor (ES/PNET) is highly malignant neoplasms composed of undifferentiated small round cells with the ability to differentiate into various tissue types. We reported the case of an 11-year-old boy who presented with unsteady gait, progressive back pain, bilateral lower limb weakness (more pronounced in the left leg), and urinary retention. Magnetic resonance imaging (MRI) demonstrated a uniformly intense extradural lesion at the T3–5 vertebral level on the left posterolateral side of the spinal canal. The lesion measured 1.35 cm × 4.8 cm on pre-contrast MRI and 4.8 cm × 1.8 cm × 1.2 cm on post-contrast imaging, causing anterior and rightward displacement of the spinal cord with associated intramedullary signal changes and moderate post-contrast enhancement. Preoperative imaging suggested possible diagnoses of lymphoma or lipovascular tumor. However, postoperative histopathological examination confirmed the diagnosis of a small round cell malignant tumor consistent with an ES/PNET. The rapid progression to intramedullary metastasis and poor outcome emphasize the need for early diagnosis and more effective treatment strategies. Spinal ES/PNET is extremely rare, and this case highlights the clinical presentation, diagnostic challenges, and histopathological features of this aggressive tumor, which remain poorly reported in the literature.